The costs of Age Management in agricultural companies - Hana URBANCOVÁ; Helena ČERMÁKOVÁ (Agricultural Economics (AGRICECON), 2015)
In view of the strengthening demographic trend of ageing of the population and the pension reform underway in the Czech Republic, the problem of Age Management, which focuses on the management taking into account the age of employees, has become very current from the perspective of securing manpower. The agricultural sector has also long been facing problems in the area of manpower. Therefore, the aim of the article is to analyse and evaluate the costs for supporting the Age Management in agricultural businesses and to propose measures leading to the effective utilization of these analysed financial means. The data were acquired on the basis of a quantitative survey with the aid of a questionnaire survey in agricultural businesses in the Czech Republic (the number of businesses: n = 436, the number of agricultural businesses: nz = 103). One of the conclusions of the article is that 24.3% of the approached agricultural businesses are implementing the Age Management. These are primarily small and medium agricultural businesses with up to 50 employees, which incur in average 6 to 10% of operational costs in relation to the gained profits on the application of the Age Management principles.